Leaky Gut Driven by Dysbiosis Augments Activation and Accumulation of Liver Macrophages via RIP3 Signaling Pathway in Autoimmune Hepatitis - Zhang, Hongxia; Liu, Man; Zhong, Weilong; Zheng, Yanping; Li, Yanni; Guo, Liping; Zhang, Yujie; Ran, Ying; Zhao, Jingwen; Zhou, Lu; Wang, Bangmao (Frontiers in Immunology, 2021)
The gut–liver axis has been increasingly recognized as a major autoimmunity modulator. However, the implications of intestinal barrier in the pathogenesis of autoimmune hepatitis (AIH) remain elusive. Here, we investigated the functional role of gut barrier and intestinal microbiota for hepatic innate immune response in AIH patients and murine models. In this study, we found that AIH patients displayed increased intestinal permeability and pronounced RIP3 activation of liver macrophages. In mice models, intestinal barrier dysfunction increased intestinal bacterial translocation, thus amplifying the hepatic RIP3-mediated innate immune response. Furthermore, GSK872 dampened RIP3 activation and ameliorated the activation and accumulation of liver macrophages in vitro and in vivo experiments. Strikingly, broad-spectrum antibiotic ablation significantly alleviated RIP3 activation and liver injury, highlighting the causal role of intestinal microbiota for disease progression. Our results provided a potentially novel mechanism of immune tolerance breakage in the liver via the gut-liver axis. In addition, we also explored the therapeutic and research potentials of regulating the intestinal microbiota for the therapy of AIH.